A mathematical model for pantograph-catenary interaction. Issue 5 (2nd September 2016) - Oumri, M.; Rachid, A.
ABSTRACT: Modelling the interaction between the pantograph and the catenary is an active field due to the development of high-speed trains. In this article, a 3D mathematical model based on finite element method is proposed to study the dynamic behaviour of the pantograph–catenary system. The equations of motion for a beam element have been discretized to obtain the weak form associated to each element of the catenary. The pantograph–catenary dynamic interaction model is implemented as a numerical simulation tool. The proposed model is compared to the performance of a commercial 3D simulator and it is faced to the requirements of the European Standard EN50318.